Control of stator voltage-controlled current source induction motor drive - Song, J.-H.; Kim, K.-B.; Youn, M.-J. (IEEE International Symposium on Industrial Electronics, 1992)
This paper presents a comprehensive study on the stability of several control schemes for the induction motor driven by current source inverters. A stator voltage-controlled current source inverter driven system without a speed sensor is investigated in order to find appropriate control schemes, which are primarily based on a direct or, alternatively, an indirect frequency control scheme. The overall control systems with either a voltage control loop or current and voltage control loops, provided in addition to each frequency control scheme, are analyzed by utilizing the root locus method and simulated by computer to show the validity of this analysis. ？ 1992 IEEE.